ISOLASI DAN IDENTIFIKASI SENYAWA GOLONGAN XANTON DARI KULIT BUAH MANGGIS ( Garcinia mangostana L.) - Ivan Surya Pradipta; Titi W Nikodemus; Yasmiwar Susilawati (Universitas Islam Indonesia, 2007)
ABSTRACTA research on the isolation and identification of xanthone from the fruit rind of mangosteen(Garcinia mangostana L.) was carried out. Extraction was done using maceration with methanol –water solvent and fractionation with n-hexane and ethyl acetate solvent. Column chromatographywith silica gel as the stationary phase and n-hexane – ethyl acetate (7 : 3) as the mobile phase wasused for the isolation. From the ethyl acetate fraction was obtained GM II-1 isolate (Rf 0,61 ; nhexane– ethyl acetate 7 : 3 as mobile phase) which showed a colour change from reddish brown toyellow under UV light 366 nm after spraying with AlCl3. Identification of the isolate with UVspectrophotometry gave maximum absorptions at wavelengths 241,5, 257,5, 317, 364,5 nm. GC -MS indicated that GM II-1 isolate had a molecular weight of 259, the isolate was presumed to be axanthone.Keywords: xanthone, Garcinia mangostana L., mangosteen, isolation, identification